2019
DOI: 10.1016/j.nutres.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis and gut microbiota dysbiosis induced by high-fat diet are reversed by 1-week chow diet administration

Abstract: Many studies have recently shown that diet and its impact on gut microbiota are closely related to obesity and metabolic diseases including nonalcoholic fatty liver disease. Gut microbiota may be an important intermediate link, causing gastrointestinal and metabolic diseases under the influence of changes in diet and genetic predisposition. The aim of this study was to assess the reversibility of liver phenotype in parallel with exploring the resilience of the mice gut microbiota by switching high-fat diet (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
1
9
2
Order By: Relevance
“…In contrast to our results, some studies have reported that dietary interventions involving a switch to healthier diets following WD can alleviate gut dysbiosis in rodents [73][74][75] and in humans [76,77]. Our results, however, show an even greater divergence in the microbiome relative to chow-fed rats after switching from either a SUG or a CAF diet to a healthy standard chow diet for ∼5 weeks, especially in the CAF animals.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, some studies have reported that dietary interventions involving a switch to healthier diets following WD can alleviate gut dysbiosis in rodents [73][74][75] and in humans [76,77]. Our results, however, show an even greater divergence in the microbiome relative to chow-fed rats after switching from either a SUG or a CAF diet to a healthy standard chow diet for ∼5 weeks, especially in the CAF animals.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, some studies have reported that dietary interventions involving a switch to healthier diets following WD can alleviate gut dysbiosis in rodents (Zhang et al, 2012;Shang et al, 2017;Safari et al, 2019) and in humans (Haro et al, 2017;Qian et al, 2020). Our results, however, show an even greater divergence in the microbiome relative to controls after switching from either a SUG or a CAF diet to a healthy control diet for ~5 weeks, especially in the CAF animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Diet is considered as one of the most critical environmental factors shaping gut microbial structures [40][41][42]. HFD feedings were observed to be linked with alterations in the gut microbial content as well as decreased diversity [19,42,43].…”
Section: Discussionmentioning
confidence: 99%